Investigation of wind wave parameters in the Black Sea coastal zone from Odessa to the Dniper estuary under various wind conditions - Alekseev, D.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
Wind waves in the Black Sea coastal zone from Odessa to the Dniper estuary are studied by using the SWAN spectral numerical model. A high space resolution is achieved due to the implementation of the nested grid technique. Parameters of waves which are generated by winds of eight basic directions and various strengths are analyzed. It is obtained that the most intensive waves in the open part of the water area are caused by south-east, south, and south-west winds, and the least intensive waves are caused by north-east, north, and north-west ones. Wave direction deflects significantly from the wind one only in cases of west and east winds. In the Dniper-Bug estuary, the maximal wave heights in cases of winds with different directions and the same strengths are close enough; only the region of their space location is changed.